2020
DOI: 10.9734/ajsspn/2020/v6i430093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Levels of Phosphorous and Zinc Fertilizers on the Yield and Nutrient Uptake of Maize (Zea mays L.) on Luvisols in Northern Guinea Savannah Region of Nigeria

Abstract: The study aimed to determine the effects of different levels of phosphorous and zinc fertilizers on the yield and nutrient uptake of maize (Zea mays L.) The experiments were  conducted in a factorial experiment under Randomized Complete Block Design (RCBD) to determine the effect of P and Zn applications on TZL white composite improved variety            of maize. Four levels of phosphorus (0, 10, 20 and 30 kg P ha-1) and three levels of zinc (0, 5 and 10kg Zn ha-1) were applied on experimental plots of 4.5m x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…Similar findings were also concluded by [23]. [24] Were of the view that enhancement in biological yield was due to the crucial role of zinc in the production of corn. Results of the study are also consistent with results obtained by [22] who found that addition of micronutrients boosted biological yield.…”
Section: Biological Yield (Kg Ha -1 )supporting
confidence: 85%
“…Similar findings were also concluded by [23]. [24] Were of the view that enhancement in biological yield was due to the crucial role of zinc in the production of corn. Results of the study are also consistent with results obtained by [22] who found that addition of micronutrients boosted biological yield.…”
Section: Biological Yield (Kg Ha -1 )supporting
confidence: 85%
“…The results of the analysis of variance in Table (7) showed that there were significant differences between the treatments, as the 50% treatment gave phosphorous, the highest average amounted to 34.86 cm², and an insignificant difference from the levels 75% and 150%, which gave two levels, amounting to 33.98 cm² and 32.72 cm², while it was significantly superior to the treatment of The control gave the lowest average of 29.72 cm². This is due to the sufficient increase in the availability of phosphorus in the soil, which increased its absorption by plants, which was reflected in the plant is particularly positive in the process of carbon metabolism, which contributes to increasing the leaf area, and this result agreed with [17]. The results of the analysis of variance in the table shown (7) indicated that there was a significant effect of the bio char treatment, as it recorded the highest average for this trait amounting to 34.48 cm² compared to the control treatment, which gave the lowest average for this trait amounting to 30.73 cm².…”
Section: Leave Area (Cm²)supporting
confidence: 64%